Photometric Follow-up of the CoRoT Mission The CoRoT Photometric Follow-Up Team - Deeg, H; Aigrain, S; Alapini, A; Alonso, R; Almenara, J; Barbieri, M; Bouchy, F; Dvorak, R; Eislffel, J; Erikson, A; Fridlund, M; Gillon, M; et al. (2009)
A short overview of the motivation and techniques of the ground-based photometric follow-up program of the CoRoT mission is given. © 2009 International Astronomical Union.